The known world - Jones, Edward P. (New York : Amistad, 2003)
When a plantation proprietor and former slave--now possessing slaves of his own--dies, his household falls apart in the wake of a slave rebellion.
Accelerated Reader AR
Keywords: African American plantation owners -- Fiction; African American slaveholders -- Fiction; Plantation life -- Fiction; Slavery -- Fiction; Slaves -- Fiction; Virginia -- Fiction; Historical fiction